(untitled) (Bulletin KNOB, 2016)
This article seeks to determine the significance of the De Hoeve country house in the oeuvre of Robert van ’t Hoff (1887–1979), and in what way the design contributes to the development of a vernacular building style in the early history of the Modern Movement in the Netherlands. In De Hoeve, erected outside the built-up area of Noordwijk-Binnen in 1913, Van ’t Hoff explored the possibilities of combining the English country house style with a national (Dutch) building style. He borrowed the aesthetic of the farmhouse buildings in the surrounding area and translated it into a country house with a modern floor plan geared to comfort and pleasurable living. For the family of the client, the Leiden publisher H.E. Stenfert Kroese, he created a salubrious living environment that specifically sought to connect with the place (road, landscape, farms), local building practices (farmhouse, brickwork, thatched roof) and a healthy family life in the countryside. In the early decades of the twentieth century, these Arts and Crafts principles offered a guideline for an alternative to the Revival styles and for the search for a new, contemporary architecture appropriate to the region. This design by Van ’t Hoff is of significance for the history of modern architecture in the Netherlands because an analysis of the country house reveals that this future member of the avant-garde’s quest for a new, modern architecture, had a lot to do with building on tradition. De Hoeve shows that the contrast between tradition and modernity within the Modern Movement was much less marked than some writers have previously supposed. The fact that Van ’t Hoff did not include the country house in his list of works, and in so doing tried to influence the historical record, is typical of Modern Movement architects, who preferred to write their own history. Now that we know how he approached the design of the De Hoeve country house in 1913, it is time for a reinterpretation of Van ’t Hoff’s other early works: the De Lindt country house (later renamed Løvdalla) in Huis ter Heide near Zeist (1911–1912), Hofstede de Zaaier in Lunteren (1911–1912), and the Augustus John studio in Chelsea, London (1913). Originally these seemed like the stylistic exercises of a young architect who was finding his way through history by trying out variations and endowing them with his own expressive power. But in the context of De Hoeve it has become clearer that during the years 1910–1913 he was searching for a typical national architecture, and was trying to reconcile traditional building methods and crafts with contemporary, modern comfort. From 1917–1918 onwards, social ideology played an increasingly important role in Van ’t Hoff’s work. Not only did he regard a pleasant and healthy living environment as a universal value. He also focused increasingly on the social world outside the family, and on the relation between work and living. He abandoned his interest in (spacious) country houses for private clients in favour of social change, and an architecture based more on the equality of human beings. The Arts and Crafts movement was also the source of inspiration for this concern with social reform.